Pengaruh Penggunaan Arang Aktif Terhadap Perubahan Warna Gigi (Studi Literatur Tentang Penggunaan Arang Aktif Dibidang Kesehatan Gigi) - Tika Puji Lestari; Denden Ridwan Chaerudin; Megananda Hiranya Putri; Isa Insanuddin (Poltekkes Kemenkes Bandung, 2022)
Tooth discoloration is a change in the color of the teeth in terms of color, hue, or translucency. One that is believed to be able to brighten teeth is activated charcoal because it can absorb stains on the teeth. This study is a descriptive study with a literature study that aims to determine the effect of using activated charcoal on tooth discoloration. The data were obtained through a literature search of 4 articles related to the use of activated charcoal as a whitening agent for discolored teeth. The results showed that activated charcoal affected whitening teeth when used by brushing your teeth with toothpaste preparations mixed with activated charcoal powder, toothpaste containing activated charcoal formula, and activated charcoal toothbrush.